Employing Aloysia citrodora (lemon verbena) as a substrate to improve toxicological and antioxidative properties of kombucha beverage - Rostami, S. F.; Roufegarinejad, L.; Karimidastjerd, A.; Khiabani, A. Habibzadeh; Toker, O. S.; Ghorbani, M. (AKADEMIAI KIADO ZRT, 2024)
This study examined the production of kombucha beverages with several combination of black tea and Aloysia citrodora. For this purpose, fi ve types of kombucha drinks were prepared using different ratios of pure black tea and pure A. citrodora (80:0, 50:30, 40:40, 30:50, and 0:80). Total phenolic and fl avonoid content, radical-scavenging capacity based on DPPH, ferric reducing antioxidant power (FRAP) in the fermentation period (days 0, 5, 10, and 15), and cytotoxicity on the 15th day have been evaluated. The results showed that phenolic and flavonoid contents and antioxidant properties increased during fermentation (P < 0.01). Using A. citrodora as a substrate enhanced the phenolic and antioxidant properties. The maximum amounts of polyphenols and flavonoids were 240.24 mg GAE/mL and 49.65 mu g QE/mL, respectively, and the DPPH value was 92.81% for the samples with an equal ratio of black tea and A. citrodora on the 15th day. In addition, this sample had the highest rate (66%) of destroying PC3 prostate cancer cells at a 600 mu g dL(-1)concentration. Using A. citrodora in kombucha drink not only improved the health indices but also caused better acceptance by the sensory evaluators compared to the sample of kombucha beverage produced with pure black tea.
Keywords: kombucha; Aloysia citrodora; free-radical scavengers; DPPH; phenolic contents; fermented beverages; FERMENTATION; Food Science & Technology; Nutrition & Dietetics